Urban development, housing market and housing policy in Leipzig - Dieter Rink (Helmholtz-Zentrum für Umweltforschung (UFZ), 2022)
[Introduction] Leipzig's urban development has been subject to serious, not to say extreme, changes in terms of shrinkage and growth over the past three decades. These had a strong impact on the housing market, which was first very tight and then (very) relaxed for some time. In recent years it has tightened up again. Whether Leipzig has a "housing question" or even a housing shortage is, however, still assessed differently and discussed controversially by relevant actors. The sometimes extreme changes in the housing market have led to several realignments in housing policy. This is reflected not least in the four quite different housing policy concepts adopted by the city council since 1990. In the wake of strong growth and the tightening of the housing market, Leipzig reoriented its housing policy in 2015 with a new concept. This paper briefly discusses the strategies of the actors and the new housing policy, the starting situation and the developments in the 1990s and 2000s in order to provide the necessary background for understanding the current developments on the housing market. Then the current situation is presented and the specifics of the housing question in Leipzig are elaborated. This is followed by a description of housing policy, its concepts and instruments, the actors and governance structures. Finally, there is a summary of the implementation steps and the difficulties encountered before a conclusion is drawn. The coronavirus pandemic has currently changed some of the parameters of development. Since these are still subject to great uncertainty at the present time, they are addressed in an excursus in which possibilities and plausibilities are discussed.
Keywords: 330; Stadtentwicklung; Bevölkerungsentwicklung; Wohnungsmarkt; Wohnungspolitik; Leipzig; Deutschland